A Cross-Gender Analysis of Lexical Hedges in the Animated Film Tinker Bell (2008) - Luh Ayu Deviana Sintya; Luh Putu Laksminy; I Gusti Ayu Gde Sosiowati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the use of lexical hedges by male and female characters in the animated film “Tinker Bell” (2008), focusing on differences in variation and communicative functions based on gender. The analysis employs Lakoff’s theory of women’s language and Holmes' framework of language functions. A qualitative descriptive method was used, with data collected through documentation and audio-visual observation from the film’s transcript. The results also indicate that although both genders employ lexical hedges, female characters tend to demonstrate a broader range of forms and functions. The findings highlight how hedges not only reflect gendered communication styles but also contribute to character development and narrative flow within the film. This study contributes to understanding gendered communication patterns in animated media and how they reflect broader sociolinguistic dynamics.